2019
DOI: 10.3389/fimmu.2019.00276
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome and Inflammatory Bowel Disease

Abstract: NLRP3 inflammasome can be widely found in epithelial cells and immune cells. The NOD-like receptors (NLRs) family member NLRP3 contains a central nucleotide-binding and oligomerization (NACHT) domain which facilitates self-oligomerization and has ATPase activity. The C-terminal conserves a leucine-rich repeats (LRRs) domain which can modulate NLRP3 activity and sense endogenous alarmins and microbial ligands. In contrast, the N-terminal pyrin domain (PYD) can account for homotypic interactions with the adaptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
333
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(340 citation statements)
references
References 105 publications
7
333
0
Order By: Relevance
“…1h). Inflammasome activation functions as an indispensable factor in the pathological process of IBD, contributing to intestinal mucosal inflammation 36 . Interestingly, berberine could suppress the expression level of NLRP3, ASC, and cleaved caspase-1 (Fig.…”
Section: Berberine Alleviated the Inflammatory Injury Of Dssinduced Cmentioning
confidence: 99%
“…1h). Inflammasome activation functions as an indispensable factor in the pathological process of IBD, contributing to intestinal mucosal inflammation 36 . Interestingly, berberine could suppress the expression level of NLRP3, ASC, and cleaved caspase-1 (Fig.…”
Section: Berberine Alleviated the Inflammatory Injury Of Dssinduced Cmentioning
confidence: 99%
“…Interestingly, a number of recent studies have highlighted the importance of NRLP3-dependent mucosal immunity also in inflammatory bowel diseases (IBD), which are frequently associated with cholestatic liver diseases. Moreover, single nucleotide polymorphisms in the NLRP3 gene have been associated with the development of both ulcerative colitis (UC) and Crohn's disease [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we showed that NLRP3 gene promoter site is significantly more methylated in the newly diagnosed jSpA patients, which can be responsible for previously observed expression alteration. While increased expression of the NLRP3 gene has been found in many autoinflammatory diseases, decreased expression has been associated with inflammatory bowel disease (IBD), a disease that shares some striking similarities with jSpA, including the gut dysbiosis [20,21]. The NLRP3 gene has a crucial role in the assembly of the NLRP3 inflammasome, an innate immune sensor that regulates Bdanger^in response to various signals [22].…”
Section: Discussionmentioning
confidence: 99%